2014
DOI: 10.1111/ecc.12162
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot testing of an online intervention to support young couples' coping and adjustment to breast cancer

Abstract: Couplelinks is an original, professionally facilitated online intervention tailored to the unique challenges facing young women with breast cancer and their male partners. The purpose of this evaluation was to determine the feasibility and acceptability of the intervention and areas for improvement. Sixteen couples were sequentially enrolled over an 18-month period. Couples provided feedback via a treatment satisfaction survey, and post-treatment interviews with a sub-group of participants. Qualitative informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
84
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(106 citation statements)
references
References 58 publications
1
84
0
4
Order By: Relevance
“…Of the total studies, 4 included only female survivors, [30-33], 1 study included only men [34], while the remaining 17 included both male and female participants [35-51]. Only 4 studies reported on the ethnicity of their participants [33,38,47,48]. Survivor cancer diagnoses included breast, lung, colorectal, ovarian, head and neck, prostate, hematological disease, and lymphoma.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the total studies, 4 included only female survivors, [30-33], 1 study included only men [34], while the remaining 17 included both male and female participants [35-51]. Only 4 studies reported on the ethnicity of their participants [33,38,47,48]. Survivor cancer diagnoses included breast, lung, colorectal, ovarian, head and neck, prostate, hematological disease, and lymphoma.…”
Section: Resultsmentioning
confidence: 99%
“…The media used within telehealth interventions were heterogeneous: 11 studies appraised telephone-based interventions, [30-32,34,35,42,43,47,49-51], 5 studies related to primarily Web-based interventions, [33,36,39,40,48], 1 study evaluated email communication [37], and 5 looked at interventions using handheld monitoring devices [38,41,44-46]. The purpose of the interventions was diverse and included: 15 which supported patients through treatment; 6 which monitored symptoms [36,38,41,44-46]; and 9 which provided psychological support, information, advice or self-management strategies [33-35,39,40,42,43,47,49]. For 2 studies, telehealth acted as a form of communication between patients and HCPs at various stages of their journey [37,48] and 5 interventions replaced clinic visits for follow-up patients [30-32,50,51].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations